Humor of the Prophet ? : In Search of a lost Book. - DR. GABOR KORVIN (Hamdard Islamicus, 2019)
Had Mohammed ?, the Holy Prophet of Islam, ever cracked a joke? This question occurred to me in the 1990s, when collecting authentic Prophetic traditions on women’s political leadership. The Pakistani Judge, Justice A. Hussain (b. 1949) , when writing about a certain ahadith about women’s alleged “deficiencies” excluding them from political roles, noted “in fact one view voiced by some eminent scholars is that the ÍadÊth in question may be a humor like the joke that the Prophet (?) said that old women shall not enter Paradise and when the old ladies felt perturbed the Prophet (?) explained that those who enter Paradise will become young.”Justice Hussain meant, of course, that as jokes are generally based on logical contradictions, according to the principles of Islamic Jurisprudence (uÎËl al-fiqh ) no valid legal conclusion can be drawn from them, even if they come from an authentic collection of ahadith.